Seasonal root development of Cabernet sauvignon grafted on different rootstocks - Kocsis, L.; Baracsi Horváthné, E.; Farkas Lajterné, B.; Kocsisné Molnár, G. (International Journal of Horticultural Science, 2014)
The minirhizotron system gives opportunity to study the root development without disturbing the soil and root. We have found certified differences in root development during the year 2013 among the rootstocks grafted on ‘Cabernet sauvignon’. The number of roots varied according to the rootstocks in different depth of soil layers and also varied the development of ripeness of the root system. We conclude that root system development is affected by soil physical and chemical properties, but differences according to the rootstock genotype on the similar type of soil exist.